Perancangan dan Pengembangan Website Bosque Barbershop untuk Reservasi dan Profil Usaha - Khoir, Muhammad Faraz Maulal; Sarmidi, Sarmidi; Saleh, Yopa Taufik (Journal Digital Technology Trend, 2026)
Bosque Barbershop operates without a structured reservation system and lacks an official website capable of presenting its business profile in a centralized manner. The existing process relies on Linktree — a link-aggregation tool that cannot handle scheduling logic or booking confirmation, leaving customers without scheduling certainty. This study developed an integrated website serving two functions: online service reservation and business profile presentation. The Research and Development (R&D) method was applied using the ADDIE development model. Data were gathered through direct observation and semi-structured interviews with the owner and administrator. The website was built using the Laravel framework, incorporating features for service reservation, scheduling, barber selection, and booking management. Functional testing via Black Box Testing confirmed that all primary features operate as specified. Feasibility assessment through TELOS analysis — covering Technical, Economic, Legal, Operational, and Schedule dimensions — placed the system in the "Very Feasible" category. The system meets its functional requirements and is operationally viable for both administrators and customers.